Aerobic Exercise Training Induces the Mitonuclear Imbalance and UPRmt in the Skeletal Muscle of Aged Mice - Cordeiro, Andre; Bricola, Rafael S.; Braga, Renata R.; Lenhare, Luciene; Silva, Vagner R. R.; Anaruma, Chadi P. [UNESP]; Katashima, Carlos K.; Crisol, Barbara M.; Simabuco, Fernando M.; Silva, Adelino S. R.; Cintra, Dennys E.; Moura, Leandro P. [UNESP]; et al. (Oxford Univ Press Inc, 2020)
The impairment of the mitochondrial functions is a hallmark of aging. During aging, there is a downregulation of two mechanisms strictly associated with mitochondrial integrity, including the mitonuclear imbalance (eg, imbalance in mitochondrial- versus nuclear-encoded mitochondrial proteins) and the mitochondrial unfolded protein response (UPRmt). Here, we evaluated the effects of aerobic exercise in the mitonuclear imbalance and UPRmt markers in the skeletal muscle of old mice. We combined the physiological tests, molecular and bioinformatic analyzes to evaluate the effects of 4 weeks of aerobic exercise training on mitonuclear imbalance and UPRmt markers in the skeletal muscle of young (2 months) and aged (24 months) C57BL/6J mice. Initially, we found that aging reduced several mitochondrial genes in the gastrocnemius muscle, and it was accompanied by the low levels of UPRmt markers, including Yme1l1 and Clpp mRNA. As expected, physical training improved the whole-body metabolism and physical performance of aged mice. The aerobic exercise increased key proteins involved in the mitochondrial biogenesis/functions (VDAC and SIRT1) along with mitochondrial-encoded genes (mtNd1, mtCytB, and mtD-Loop) in the skeletal muscle of old mice. Interestingly, aerobic exercise induced the mitonuclear imbalance, increasing MTCO1/ATP5a ratio and UPRmt markers in the skeletal muscle, including HSP60, Lonp1, and Yme1L1 protein levels in the gastrocnemius muscle of aged mice. These data demonstrate that aerobic exercise training induced mitonuclear imbalance and UPRmt in the skeletal muscle during aging. These phenomena could be involved in the improvement of the mitochondrial metabolism and oxidative capacity in aged individuals.
Keywords: Aging; Mitonuclear imbalance; UPRmt; Skeletal muscle; Physical exercise